Facial Recognition Payment System: An Effortless Payment Method in Public Transport Sector - Yee Fei, Ng; Reka Ramachandiran, Chandra (International Journal of Psychosocial Rehabilitation, 2019)
From the beginning, the traditional way of using public transport in Malaysia is only able to use physical cash to purchase a ticket. The technology nowadays is increase rapidly which transform to make payment from using cash to smart cards to prove their transactions. This transformation can save plenty of time, however, there are still some flaws of current technology. First of all, they will be charged a penalty if passengers have lost their physical ticket or card, and this may cause passengers to pay extra and not be able to arrive at the destination on time. Furthermore, passengers who buying a ticket manually have to wait a very long queue during peak session, such as working hours and public holidays, and this could cause the passenger a lot of inconvenience. To overcome these problems, this paper offers a new technology to enables passengers can ease to use and feel convenience to make payment in public transport by using facial recognition. This new technology was used in other countries, such as the purpose of security, but was never used in Malaysia. This paper also provides the methodology for gathering user acceptance in this new technology using interview and simple random sampling to evaluate the data. Overall, the payment system for facial recognition is the fastest and simplest way to improve efficiency in the public transport ticketing system